The Current Regulatory Framework Governing Business in Bulgaria - O'Brien, Thomas; Filipov, Christian (Washington, DC: World Bank, 2013)
The paper identifies the key elements of the regulatory environment for business in Bulgaria, to serve as a research guide, while recognizing that the rapid development of new legislative, and regulatory procedures, are greatly needed, largely to meet the European Union's (EU) legal, and regulatory standards. It describes business creation, with the Commercial Code providing much of the central, comprehensive regulation. Also, another route for business creation in the private sector has been offered through the privatization process of state-owned assets, and, the use of concessions can also be viewed as another route to the creation of private business. However, and although concession legislation sets an overall framework of reasonable adequacy, reports from practitioners in the marketplace reveal much remains to be done to forward this agenda. In regulating corporate operations, the stake of shareholders in the formation of corporate policy, reflects shared participation in the corporate capital base; thus to engender confidence in corporate management standards, and underpin the broadening of share ownership, priority actions should take place. Bulgarian competition law, follows EU doctrine, which penalizes companies for discriminatory behavior, monitored by the Commission on the Protection of Competition, with defined discretionary powers. The study further highlights accounting standards, investment channels, and the tax regime, suggesting priority actions for company transformation such as enhanced training for judges, and court administration procedures to rationalize the case load. Overall, recommendations include accurate drafting of primary legislation; quality improvement of secondary legislation, setting the pace for a timely implementation, as well as a more effective judicial system for corporate affairs, and services delivered by the public administration to businesses.